A recommendation for earlier screening of type 2 diabetes mellitus within the US population: A cross-sectional analysis of NHIS data. (October 2020) - Greiner, Benjamin; Mercer, Heather; Raymond, Charissa; Sonstein, Lindsay; Hartwell, Micah
Abstract: Diabetes is a leading cause of morbidity and mortality in the US. Current USPSTF guidelines recommend screening asymptomatic, overweight patients greater than 40 years. Our study showed that ¼ of patients with type 2 diabetes were diagnosed prior to 40 years. Therefore, we recommend lowering the screening age for diabetes.